Using Mobile Apps for Health Management: A New Health Care Mode in China - Lv, Qing; Jiang, Yutong; Qi, Jun; Zhang, Yanli; Zhang, Xi; Fang, Linkai; Tu, Liudan; Yang, Mingcan; Liao, Zetao; Zhao, Minjing; Guo, Xinghua; Qiu, Minli; et al. (JMIR Publications, 2019)
BackgroundChina has a large population; however, medical resources are unevenly distributed and extremely limited, and more medical services are needed. With the development and ever-increasing popularity of mobile internet communication, China has created a mode of mobile health (mHealth) care to resolve this problem. ObjectiveThe aim of this study was (1) to describe the problems associated with China's medical care practice, (2) explore the need for and the feasibility of internet-based medical care in China, and (3) analyze the functionality of and services offered by internet-based health care platforms for the management of chronic diseases. MethodsData search was performed by searching national websites, the popular search engine Baidu, the App Store, and websites of internet medical care institutions, using search terms like "mobile health," "Internet health," "mobile medical," "Internet medical," "digital medical," "digital health," and "online doctor." A total of 6 mobile apps and websites with the biggest enrollment targeting doctors and end users with chronic diseases in China were selected. ResultsWe recognized the limitations of medical and health care providers and unequal distribution of medical resources in China. An mHealth care platform is a novel and efficient way for doctors and patients to follow up and manage chronic diseases. Services offered by these platforms include reservation and payment, medical consultation, medical education assessment, pharmaceutical and medical instruments sales, electronic medical records, and chronic disease management. China's health policies are now strongly promoting the implementation of mHealth solutions, particularly in response to the increasing burden of chronic diseases and aging in the population. ConclusionsChina's internet-based medical and health care mode can benefit the populace by providing people with high-quality medical resources. This can help other countries and regions with high population density and unevenly distributed medical resources manage their health care concerns.